The neuroprotective effect of ascorbic acid against imidacloprid-induced neurotoxicity and the role of HO-1 in mice - Mudgal, Rajat; Sharma, Satyam; Singh, Sanjiv; Ravichandiran, V. (Frontiers in Neurology, 2023)
Imidacloprid (IMI) is not only a neurotoxic agricultural pesticide but also a possible food contaminant. The aims of this study were to (1) explore the relationship between recurrent IMI administration and neuronal toxicity in mice and (2) evaluate the potential neuroprotective effect of ascorbic acid (AA), a substance with significant free radical scavenger and having property to block the inflammatory pathways. Mice were categorized as naïve controls (administered vehicles for 28 days); the IMI-treatment animal group (administered po 45-mg/kg body weight of IMI per day for 28 days); and the IMI + AA treatment animal group (administered the same IMI dose + 200 mg/kg of AA orally for 28 days). On day 28, memory losses were assessed using the Y-maze and novel target identification behavioral tests. Mice were sacrificed 24 h after the final IMI treatments, as well as hippocampus tissues, were utilized to determine histological assessments, oxidative stress biomarkers, and Heme oxygenase-1 (HO-1) and nuclear factor erythroid 2-related factor 2 (Nrf2) gene expression levels. The findings demonstrated that IMI-treated mice had substantial impairment of spatial and non-spatial memory functions, as well as reduced antioxidant enzyme and acetylcholinesterase activity. The AA neuroprotective action was achieved through the suppression of the HO-1 expression as well as the stimulation of Nrf2 expression in hippocampal tissues. In summary, recurrent IMI exposure causes oxidative stress and neurotoxicity in mice, and the administration of AA significantly reduces the IMI toxicity possibly by the activation of the HO-1/Nrf2 pathway.